2014
DOI: 10.1111/mec.12647
|View full text |Cite
|
Sign up to set email alerts
|

Balancing selection and heterozygote advantage in major histocompatibility complex loci of the bottlenecked Finnish wolf population

Abstract: Maintaining effective immune response is an essential factor in the survival of small populations. One of the most important immune gene regions is the highly polymorphic major histocompatibility complex (MHC). We investigated how a population bottleneck and recovery have influenced the diversity and selection in three MHC class II loci, DLA-DRB1, DLA-DQA1 and DLA-DQB1, in the Finnish wolf population. We studied the larger Russian Karelian wolf population for comparison and used 17 microsatellite markers as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 85 publications
11
70
0
Order By: Relevance
“…Niskanen et al . ) by types of balancing selection such as heterozygote advantage, frequency‐dependent selection and variable selection in time and space (Hedrick ).…”
Section: Introductionmentioning
confidence: 99%
“…Niskanen et al . ) by types of balancing selection such as heterozygote advantage, frequency‐dependent selection and variable selection in time and space (Hedrick ).…”
Section: Introductionmentioning
confidence: 99%
“…In grey wolves, variation in MHC genes in individuals from Croatia and Finland was compatible with balancing selection (Niskanen et al. ), while in the Scandinavian grey wolf population, variation in MHC genes was compatible with expectations under neutrality, probably as a consequence of only three adults contributing to the re‐establishment of this population (Seddon & Ellegren ). Niskanen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Niskanen et al. () found that grey wolves from Finland that were heterozygote for three MHC class II genes were less often infected by Trichinella spp., and carriers of specific MHC alleles, SNP haplotypes, and SNP alleles had fewer helminth infections, in what is a compelling example linking genetic variation with disease resistance. Another example of adaptive variation in grey wolves comes from the presence of a dominant allele in a beta‐defensin locus ( CBD103 or K locus), which makes the carrier of the allele black (Anderson et al.…”
Section: Resultsmentioning
confidence: 99%
“…The distance between DLA-DRB1 and DLA-DQA1 is 56.6 kb, while the distance between DLA-DQA1 and DLA-DQB1 is 77.7 kb. A previously established protocol [13] was used to sequence the loci in a cohort of 253 dogs. In addition, data from 41 families with 192 puppies from an earlier study by Kennedy et al [34] plus a further 12 families with 64 puppies from Rowan [35] were included.…”
Section: Methodsmentioning
confidence: 99%
“…MHC diversity differs from breed to breed and is often low [12], probably due to drift effects in small populations. However, even without free mate choice, MHC diversity in a dog breed can be close to the diversity of a wild wolf population [13, 14]. Humans have had major impact in some of the aspects that may influence the dog MHC diversity, for instance, through veterinary care and mate choice.…”
Section: Introductionmentioning
confidence: 99%